JUSTIFICATION OF THE MECHANICAL ENGINEERING ENTERPRISE PRICING STRATEGY DIRECTIONS (Вестник университета)
The problem of formation of price policy as one of components of the general strategy of the enterprise of mechanical engineering is considered. Special attention is paid to accounting of in ationary processes when planning the prices of the released goods and also to forecasting in ationary expectation. Planning of the price of goods adjusted for in ation is carried out by authors of article taking into account indexation of cost of all resources. The main directions of development of rational price policy of the enterprise in the conditions of in ation are presented.